Games in the Classroom: More Than Just Having Fun - Raúl Alberto Mora; María Catalina Lopera Gómez (Asociación Colombiana de Profesores de Ingles, 2016)
If your students have never asked you to play a game, we can tell you they are probably lying. Games and fun activities have always been one of everybody's favorite things to do in class, both for teachers and students. Nevertheless, they are usually just a way to create a relaxed atmosphere or even because we just could not come up with a better idea for that day.